1982
DOI: 10.1002/1097-0142(19821015)50:8<1568::aid-cncr2820500817>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal differentiation in trigeminal neurilemmoma

Abstract: An unusual neurilemmoma of the trigeminal nerve in a 31‐year‐old woman is described. The neoplasm was roentgenographically calcified and contained various types of mesenchymal tissue, including a cavernous angioma, cartilage, bone, and adipose tissue. Angioma in combination with neurilemmoma occurs more frequently than other forms of mesenchymal tissue. Lipoma is an uncommon component of neoplasms affecting the cranial nerves. Cartilage and bone are rarely encountered in benign intracranial neurilemmomas. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Other mesenchymal components, such as angiosarcoma or liposarcoma, may be identified but less often (D' Agostino et al, 1963b;Chaudhuri, Ronan & Manaligod, 1980;Ducatman & Scheithauer, 1984). A similar phenomenon is also very occasionally seen in benign neural neoplasms, being usually rhabdomyomatous in nature (although some would regard these benign 'Triton' tumours as hamartomas) (Kasantikul, Brown &Netsky, 1982;Markel& Enzinger, 1982;Azzopardi e?a/., 1983;Enzinger & Weiss, 1983;Hcrak, Szcntirmary & Sugar, 1983).…”
Section: Discussionmentioning
confidence: 98%
“…Other mesenchymal components, such as angiosarcoma or liposarcoma, may be identified but less often (D' Agostino et al, 1963b;Chaudhuri, Ronan & Manaligod, 1980;Ducatman & Scheithauer, 1984). A similar phenomenon is also very occasionally seen in benign neural neoplasms, being usually rhabdomyomatous in nature (although some would regard these benign 'Triton' tumours as hamartomas) (Kasantikul, Brown &Netsky, 1982;Markel& Enzinger, 1982;Azzopardi e?a/., 1983;Enzinger & Weiss, 1983;Hcrak, Szcntirmary & Sugar, 1983).…”
Section: Discussionmentioning
confidence: 98%
“…In the 15 years since the first publication, Lnf pathogenesis remains obscure. Besides neurofibromas, the presence of adipocytes may occur in other tumors of neuroectodermal origin, that is, schwannoma, perineurioma, and melanocytic nevi . Eng et al studying melanocytic nevi with adipocytes, concluded that occurrence of fat cells within nevi is probably a multifactorial process, and suggested that increased overall body fat and interactions of endogenous hormones, cytokines, or both (i.e., leptin, insulin, glucagon, fructose, and thyroid hormone) may be related to the presence of adipocytes in those lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is likely that the adipocytes in the tumor derive from the tumor cells themselves, adipocytic differentiation or lipometaplasia. Although the occurrence of divergent differentiation is a relatively uncommon event in neuroectodermal tumors, lipomatous change has been previously observed in neurofibroma, 6,7 schwannoma, 8–10 neurocytoma, 11,12 medulloblastoma, 13,14 astrocytoma, 15,16 ependymoma, 17 and primitive neuroectodermal tumor 18 . Because the neural crest is considered ectomesenchyme capable of differentiating into various cell types, tumor cells originating in the neural crest may have the capacity of lipomatous differentiation.…”
Section: Discussionmentioning
confidence: 97%